Reorientation of PRA for Integrated Watershed Development - Sudhishri, Susama; Choudhury, P.R.; Patnaik, U.S. (Journal of Soil and Water Conservation, 2022)
Participatory integrated watershed approach has been accepted as the most reliable tool to achieve sustainable rural development. PRA reinforces such watershed planning through participatory assessment of the existing natural resources, their potential and relationship with inhabitants and other resources. It helps to understand the problems, priorities, preferences and social complexities, which are key inputs for realistic development planning. However, the methodologies and techniques of PRA have to be reoriented with some cosmetic surgeries as per watershed priorities to provide effective planning inputs to micro-planners and enhance the knowledge base of the farmers. Addition of tools like soil and hydrology map, land capability perception, CPR, energy flow and ethno-botanical maps can further the explorations to augment better participatory planning and monitoring. PRA tools also can be utilized to increase the efficacy of watershed programmes through participatory impact monitoring.